Cultural Capital: The Rise and Fall of Creative Britain (Robert Hewison: Verso Books, 2014) - Power, Claire (Irish Journal of Arts Management and Cultural Policy, 2017)
A review of Robert Hewison’s Cultural Capital: The Rise and Fall of Creative Britain, which provides a cultural historian’s perspective on publically funded culture in Britain from 1997 to 2012 Robert Hewison’s latest book provides a cultural historian’s perspective on publically funded culture in Britain from 1997 to 2012. What emerges over this two hundred and thirty-four page narrative of a particular period in British cultural history – from Cool Britannia at the end of the twentieth century through to the splendor of the Olympics in 2012 – is a considered reflection on the relationship between publically funded culture and the State. It raises interesting questions for anyone either working with or interested in cultural policy, and in view of Ireland’s recently published Culture 2025 policy framework, the book makes for an educational read. It counts the true costs of what happens when government takes a direct interest in arts and culture for the pursuit of other policy aims. Ominously, as Hewison forewarns us, ‘the lesson of this is: be careful what you wish for’ (p. 3).